Pengaruh Financial Literacy, Fintech Payment, dan Marketplace Tiktok Shop Terhadap Financial Behavior pada Mahasiswa S1 Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya - Julianingtyas, Diaz Eka; Listiadi, Agung (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Students are one of the agents of change who will be used as pioneers or examples for the community. However, over time the quality and financial behavior of students can be said to go up and down because the ease of digital technology has an impact on financial behavior in everyday life. This study aims to determine the effect of financial literacy, fintech payment, and tiktok shop marketplace on financial behavior in undergraduate students of the Faculty of Economics and Business, Surabaya State University. This type of research is quantitative using primary data sourced from respondents' answers. The population of this study were undergraduate students of the Faculty of Economics and Business, Surabaya State University with probability sampling technique and 64 respondents were obtained as samples in this study. This research data was processed using IBM SPSS Statictics 22 software and analyzed using multiple linear regression methods. The results showed that the financial literacy variable had a significant negative effect on financial behavior. Meanwhile, the fintech payment variable and the tiktok shop marketplace have no significant effect on financial behavior. Financial literacy has a negative influence because students tend to not understand the meaning of financial literacy well. Fintech payment and marketplace tiktok shop have a positive influence because in the modern era that is all digital it is required to keep up with modern developments.